DESIGN ULANG KEMASAN PRODUK KOPI INDUSTRI BUKIT HITAM COFFE - Yuwita, Fitri; Uker, Damres; Zuki, Meizul; Fatharani, Arina; Anis, Ulfah (Jurnal Abdi Insani, 2024)
Coffee is a plantation commodity that plays an important role in contributing to foreign exchange and state income, as a source of income for farmers, creating jobs, driving the growth of the agribusiness and agro-industrial sectors. Bengkulu is one of the regions that has the most small industrial businesses in processing coffee, one of which is a small and medium industrial business with the Bukit Hitam Coffe brand. Keywords: Design, Packing, Coffee. Along with the development of technology, this industry has obstacles in packaging and product labels have not complied with Indonesian National Standards. In this community service activity, a redesign of ground coffee packaging was carried out. The packaging on products that have been produced before is less clear and the color is less attractive. The method of community service activities uses survey, discussion and direct practice methods. The service team conducted an initial survey and discussion with partners known some of the obstacles faced by partners, then redesigned the packaging according to the discussions that had been carried out then direct practice. The result of this activity is a packaging redesign by the service team which later this packaging can be realized and printed in the form of stickers and standing pouch packaging. The new packaging looks more elegant, the taste and aroma of coffee is not easily damaged and will later increase the shelf life. After the new packaging design was obtained, the service team conducted an evaluation. Evaluation is carried out to measure the effectiveness of the activities that have been carried out to partners. Business partners have new packaging, this packaging can be realized so that the product display is more informative than the previous packaging and logo.